PENCEGAHAN PENCEMARAN LINGKUNGAN MELALUI PENGELOLAAN SAMPAH SISTEM REDUCE, REUSE DAN RECYCLE - Lukman; Supriadi; Insarullah (TADULAKO MASTER LAW JOURNAL, 2024)
The purpose of writing is to find out the efforts of the Palu City Government to involve the community in waste management and to find out the application of Palu City Regional Regulation Number 3 of 2016 concerning Amendments to Regional Regulation Number 11 of 2013 concerning Waste Management, in an effort to prevent environmental pollution caused by waste through landfills. Waste Management Reduce, Reuse and Recycle (TPS3R). The research method uses empirical legal research methods with a Socio-juridical approach (Socio Legal Research), the data sources come from primary data and secondary data. The location of the research was carried out in Palu City, while the sample and location of this research was carried out in the Ulujadi District, Silae Village. The research population consisted of TPS3R waste customers, non-customers, TPS3R officers and the Silae Village Government and the Palu City Environmental Service (DLH). The data analysis used is qualitative. The results showed 1). The existence of the Palu City Government's efforts to involve the community, this still needs to be optimized, because what affects community involvement as waste customers is the lack of waste transport fleet facilities. 2). The effective implementation of Palu City Regulation Number 3 of 2016 concerning Amendments to Regional Regulation Number 11 of 2013 concerning Waste Management, this still needs to be optimized by socializing regulations through banners, billboards and electronic media to the public.